DEVELOPMENT OF ALPHABET BLOCK MEDIA FOR BEGINNING READING LEARNING IN CLASS I ELEMENTARY SCHOOL : Teriavegi64@gmail.com - Vegi Teria Sofiandira; Desy Anindia; Sripit Widiasttuti (Universitas Islam Balitar, 2023)
Study Program Teaching Faculty of Education Science Balitar Islamic University Advisor (I) Desy Anindia, M.Pd.I. Advisor (II) Sripit Widiastuti, S.Pd,. M.Pd.This research has a background in the low ability to recognize students' letters with low interest in reading as well, so additional learning media is needed besides books and worksheets that are commonly used in schools. The purpose of this study was to show the feasibility of the media and to find out the readability of teachers and students towards alphabet block media in the ability to recognize letters, so as to be able to develop early reading skills in grade 1 elementary school children.Data collection techniques by conducting questionnaire observations and interviews using the Research and development (R & D) method approach with 7 research steps. Data collection was carried out on 60 grade 1 elementary school students in 3 schools, namely SDN Sidorejo 01, SDN Doko 01 and SDN Doko 02 along with their class teachers.The results of the feasibility analysis of the media through 3 validators obtained a percentage with an average value of 94.29%, material and language experts obtained a percentage with an average value of 95.00%. From the results of the media feasibility analysis by 3 media expert validators, 3 material and language expert validators on product development which were then tested by conducting field practice to analyze the readability of teachers and students towards the media as teaching materials for beginning reading learning materials. In the teacher readability test, the results obtained were 93.94% & student readability was 90.44% with a very decent category. The results of the validation and readability stated that the alphabet block learning media was included in the very feasible criteria with an achievement level of 81% - 100%.